Mergers and Acquisitions by Emerging Country Multinational Companies - Yüce, Ayşe (Asian Economic and Financial Review, 2016)
This paper investigates the mergers and acquisitions by the emerging country multinational companies. Emerging country multinational companies do not have access to big amounts of capital as many developed country multinational companies. These companies can decide to engage in mergers and acquisitions with those of the other emerging country multinational companies in order to increase their profitability and competitiveness. We examine whether or not emerging country multinationals earn high and significant positive abnormal returns as a result of merger and acquisitions and we also investigate whether or not the return patterns of the emerging country multinationals are different than those of the developed country companies.